PENGARUH DISPILIN, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI PT. INDONESIA EPSON - Ulfa Afifa; Muhammad Patrialis Akbar; Aurora Oktaviani Putri Hidayat; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
The laim lof lthis lresearch lis lto lstudy lhow lcompensation, lwork lmotivation land lwork ldiscipline limpact lthe lperformance lof lPT lIndonesia lEpson lIndustry lemployees. lThis lresearch lapplies la lquantitative lapproach. lThis lresearch linvolved lemployees lof lPT lIndonesia lEpson lIndustry lin lthe lAssembling ldepartment, land lsaturated lsampling ltechniques lwere lused lto lcollect l40 lrespondents. lThis lresearch luses la lquestionnaire las la ltool. lThis lresearch luses lmultiple llinear lregression las la ldata lanalysis lmethod. lApart lfrom lthat, lthe ldata lprocessing ltool lused lis lthe lStatistical lProgram lfor lSocial lScience l(SPSS). lThe lresearch lresults lshow lthat lwork ldiscipline lhas la lpositive land lsignificant leffect lon lemployee lperformance, lwork lmotivation lhas la lpositive land lsignificant leffect lon lemployee lperformance, land lcompensation lhas la lpositive land lsignificant leffect lon lemployee lperformance. lAccording lto lthe lresults lof lthis lresearch, lmanagement lpractices lthat lcan lbe lutilized lby lrelevant lcompanies lmust ltake linto laccount lwork ldiscipline land lwork lmotivation. lEmployees lwill lbe lmore lmotivated lto ldo ltheir lbest lif lthey lreceive lappropriate ltraining land lrewards.